PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H. (The Accounting Review, 1960)
The article presents problems that were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (C.P.A.) and were presented as the first half of the C.P.A. examination in accounting practice on May 18, 1960. One of the questions asked was regarding Houston Factors Inc. The company was incorporated on December 31, 1959. The capital stock of the company consists of 100,000 shares of $10 par value each, all of which was paid in at par. The company was organized for the purpose of factoring the accounts receivable of various businesses requiring this service. The paper asks to prepare a balance sheet and an income statement for Houston Factors Inc. as at March 31, 1960. The Rickard Co.'s fiscal year ended March 31, 1960. Your examination the preceding year disclosed that the internal control was weak. The staff and organization was unchanged. The office manager was unable to reconcile the bank statements at March 31st, and opened an account called "Exchange" for $170 in order to balance his preliminary trial balance. The paper asks to reconcile both bank balances to the adjusted cash balances as of March 31, 1960.